Role of glutamine administration on T-cell derived inflammatory response after cardiopulmonary bypass - Engel, J.M.; Pitz, S.; Mühling, J.; Menges, T.; Martens, F.; Kwapisz, M.; Hempelmann, G. (Clinical nutrition (Edinburgh, Scotland), 2009)
Cardiac surgery provokes an inflammatory response for which the endothelium, the myocardium, and monocytes/macrophages are primarily responsible. T cells are altered in a different way whereby the pro-inflammatory pathway is suppressed. From the results of experimental studies it was concluded that glutamine (Gln) enhances the production of T-cell cytokines in conditions of Gln deprivation. The aim of this clinical study was to evaluate the role of a perioperative Gln infusion on intracellular inflammatory T-cell cytokine expression in patients undergoing elective cardiac surgery and to evaluate the effects on systemic inflammation, organ dysfunction and ICU length of stay. In this prospective, randomized, double-blind study, we included 78 patients (age level older than 70 years, ejection fraction less than 40%, or mitral valve replacement) undergoing elective cardiosurgery with cardiopulmonary bypass. We randomly assigned each subject to receive an infusion with either Gln (0.5 g/kg/day, group A) or an isonitrogenous, isocaloric, isovolemic nutritional solution (group B) or physiological NaCl 0.9% (group C, to eliminate an unspecific nutritional effect). We started the infusion after the induction of anesthesia with 1000 ml/24 h and maintained this state for 3 days. On the first postoperative day plasma Gln levels in group A were significantly increased (958 ± 331 μM) compared to group B (527 ± 105 μM) and group C (489 ± 104 μM), and remained higher until the third postoperative day. At the beginning and after surgery intracellular interleukin (IL)-1, IL-6, IL-8, and tumor necrosis factor-α levels in T cells showed no differences between the groups. Also, no differences could be observed with regard to C-reactive protein, SOFA score, heart and circulation support, postoperative ventilation time, and ICU length of stay. The elevation of Gln plasma levels as a result of 0.5 g/kg/day perioperative Gln infusion has no influence on the T-cell derived inflammatory response, indicating a sufficient supply of Gln. A Gln supplementation in cardiac surgery patients without a clear Gln deficiency seems not to affect the intracellular inflammatory T-cell cytokine expression.